Makna dan Fungsi Tradisi Upah-Upah dalam Masyarakat Desa Batas Kecamatan Tambusai Kabupaten Rokan Hulu - Nofrita, Misra; Arianti, Rita; Ningsih, Asih Ria; Hermawan, Hermawan; Nuratika, Nuratika (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
In Rokan Hulu, there is a unique tradition called Upah-upah. This tradition is interesting to research because it is still used today which serves to restore the spirit. The aim of this study was to describe the form and function of the upah-upah tradition in Batas village. In this study the authors used qualitative methods. The steps for collecting data are, first, making observations regarding the selection of informants taken for research. Second, conduct interviews with informants regarding upah-upahs in Batas village by recording them. Third, transcribe the recording results. Fourth, process the data that has been transcribed and fifth, make an analysis of the results of the data that has been transcribed. The results of research on the meaning and function of the upah-upah tradition of the people of Batas Village, Tambusai District, Rokan Hulu Regency, concluded that the meaning contained in the upah-upah tradition is as a form of gratitude for what God has given, whether in the form of safety from disasters, after giving birth and when starting a new life. Apart from that, the function of the Upah-upah tradition for the people of Batas Village is, first, to restore enthusiasm. Second, provide self-confidence to people who are being paid. Third, welcoming and giving thanks for someone's life journey. Apart from that, wages are used as a tradition to restore or restore a person's enthusiasm, such as after an accident, after giving birth, wages after marriage, wages after completing a treatment, wages after graduating from college, and wages after graduating from college. finished circumcision.